Current energetic particle sensors. Issue 9 (23rd September 2016) - Fennell, J. F.; Blake, J. B.; Claudepierre, S.; Mazur, J.; Kanekal, S.; O'Brien, P.; Baker, D.; Crain, W.; Mabry, D.; Clemmons, J.
Abstract: Several energetic particle sensors designed to make measurements in the current decade are described and their technology and capabilities discussed and demonstrated. Most of these instruments are already on orbit or approaching launch. These include the Magnetic Electron Ion Spectrometers (MagEIS) and the Relativistic Electron Proton Telescope (REPT) that are flying on the Van Allen Probes, the Fly's Eye Electron Proton Spectrometers (FEEPS) flying on the Magnetospheric Multiscale (MMS) mission, and Dosimeters flying on the AC6 Cubesat mission. We focus mostly on the electron measurement capability of these sensors while providing summary comments of their ion measurement capabilities if they have any. Key Points: Sensors described represent state of the art for radiation belt measurements Cubesat and microdosimeters provide new ways to monitor space weather effects Cubesat sensors nearly match capabilities of state of the art sensors